PENGARUH LITERASI KEUANGAN, RISK TOLERANCE, DAN STATUS PEKERJAAN TERHADAP KEPUTUSAN INVESTASI IRT - Dwi, Melita; Kusuma, Dewi (Catholic University Musi Charitas, 2020)
Many factors may effect investors in making investment decisions, some of them are financial literacy, risk tolerance, and employment status. These factors are thought to have an influence on investment decision. The purpose of this study was to examine the effects of financial literacy, risk tolerance, and employment status on investment decisions of Krembangan Village, Panjatan District, Kulon Progo Regency. This research used snowball sampling method. The research object of this are housewife who lives in Krembangan Village, Panjatan District, Kulon Progo Regency. There are 100 respondents taken from questionnaire by survey method. To answer the problem and test the hypotheses proposed in this study, the researchers used multiple regression analysis. The results of this study showed that financial literacy, risk tolerance, and employment status simultaneously have a significant influence on investment decisions, and financial literacy has a partially positive effect in investment decisions, risk tolerance has a partially negative influence on investment decisions, but employment status has partially no influence on investment decisions.